Revisão do gênero Aspidobothrus Reuter, 1907 com ênfase na genitália externa de machos e fêmeas (Hemiptera: Miridae) - Felippe, Maria Luiza (1983)
Revision of the genus Aspidobothrus Reuter, 1907 (Hemiptera, Miridae) with a detailed study of the present eight species. Descriptions of the genus, species and genital structures of males and females were made, including measurements of the series and also general considerations are provided. The genital structures, showing specific differences, are illustrated and discussed. A systematic key is presented, to identify the species of the genus, based on the external morphological characters. Two species, Aspidobothrus rarus Carvalho, 1950 e Aspidobothrus semiluteus (Stal, 1860), previously included in this genus, have been recently transfered by Carvalho & Felippe to other related genera (paper presented for publication in the " Revista Brasileira de Biologia, Academia Brasileira de Ciências"). Aspidobothrus latipennis Reuter, 1907 is considered to be a synonyme of Aspidobothrus designatus (Distant, 1888). The sintypes of Eccritotarsus ruficeps Berg, 1878, from Misiones, are considered as Aspidobothrus flavicostus Carvalho, 1949.